SAT0375 ICOS-ICOSL Modulates Tertiary Lymphoid Organ Formation, Regulating the Lymphotoxin Pathway in an Animal Model of SjÖgren's Syndrome. (9th June 2015) - Campos, J.; Nayar, S.; Chung, M.-M.; Withers, D.R.; Carlesso, G.; Herbst, R.; Buckley, C.D.; Barone, F.
Abstract : Background: Costimulation via ICOS-ICOSL interaction is critical for germinal center reaction in secondary lymphoid organs, regulating T cell activation and maturation into cytokine-producing cells. In autoimmunity this signal has been extensively investigated and believed to contribute to the development of follicular T helper cells, autoreactive B cells and autoantibody production. Blocking ICOS-ICOSL interaction amelliorates disease in animal models of systemic lupus erythematosus and rheumatoid arthritis. Objectives: To dissect the role of ICOS-ICOSL pathway in a animal model of tertiary lymphiod organ (TLO) formation that mimics Sjögren's syndrome. Methods: Submandibular glands of wild-type (wt), ICOSL, CD3ɛ and p55/75 (TNFR1) knockout (KO) mice were intra-ductally cannulated with luciferase-encoding replication-deficient adenovirus to induce TLO formation as previously described (1). A combination of immunofluorescence, quantitative RT-PCR, flow cytometry on digested salivary glands and in vitro mixed culture of lymphocytes and stroma were used. Results: We demonstrated that early post cannulation with adenovirus ICOSL is significantly upregulated within the salivary glands of infected mice on a population of activated stromal cells that express gp38, adhesion molecules, TNFR1 and TNFR2. In vivo experiments in ICOSLKO, CD3ɛKO and p55/75KO revealed a dramatic defect in TLO formation and reduced levels of ectopic lymphoid chemokines. ICOSL+ stromal cells stimulated effector T cells to produce lymphotoxin alpha (LTα) that in turn stimulates production of lymphoid chemokines by TNFR1+ stromal cells. These observations were further confirmed in vitro, in mixed co-cultures of lymphocytes, dendritic cells and stromal cells isolated from wt and ICOSLKO mice. This mechanism was further validated by inducing TLO formation in ICOSLKO reconstituted with wt bone marrow, that as predicted, showed a similar degree of impairment in the LTα/TNFR1 pathway as observed in the ICOSLKO mice. Conclusions: Collectively, these data demonstrate that ICOSL expression by stromal cells supports the up-regulation of LTα on T cells that in turn is required for chemokine expression via TNFR1 stimulation. These data provide a novel mechanism of action between ICOSL on stromal cells, ICOS on T cells and LTα pathways in the context of TLO formation. References: Bombardieri, Barone et al. JI. 2012 Disclosure of Interest: None declared